Neuroprotection targeting protein misfolding on chronic cerebral hypoperfusion in the context of metabolic syndrome - Herrera, María Inés (2018)
Fil: Herrera, María I. Universidad Católica Argentina. Facultad de Psicología y Psicopedagogía. Centro de Investigaciones en Psicología y Psicopedagogía; Argentina